Marias: design thinking e acolhimento para as profissionais da linha de frente dos casos de violência doméstica - Lima, Jéssica de (My University, 2021)
The issue of domestic violence has countless layers to be worked on. It is known that the records of police reports grow every year, as does the number of women assaulted by their partners and the number of victims of femicide. With the pandemic there was an aggravating factor in this number and a drop in the police report, this was due to the fact that the victim spends most of the time with his aggressor at home. This problem affects many areas, especially those who take care of these women within specialized shelters. These professionals are exhausted not only because of the cases they attend, but also with their personal life, and now, one more aggravating factor for the pandemic. Amidst all this problem, the question is: who takes care of these women? Therefore, this work aims to develop a service, brand and product project that contributes to the development of a space for speaking, listening and welcoming these professionals. To propose solutions to the problem, the Design Thinking methodology was used in the project. The result was the development of a brand - product - service system that aims to promote this welcoming environment, through: a service that collaborates with the management of emotional issues for professionals; a product that relates to the movement of going to the streets to claim rights; and a brand that the public recognizes. [resumo fornecido pelo autor]
A problemática da violência doméstica possui inúmeras camadas para serem trabalhadas. Sabe-se que os registros de boletins de ocorrências crescem a cada ano, assim como o número de mulheres agredidas por seus companheiros e o número de vítimas de feminicídios. Com a pandemia houve um agravante nesse número e uma baixa nos BOs, isso se deu pelo fato da vítima estar maior parte do tempo com seu agressor dentro de casa. Esse problema afeta muitas áreas, principalmente quem cuida dessas mulheres dentro de abrigos especializados. Essas profissionais estão exaustas não somente por conta dos casos que atendem, mas também com sua vida pessoal, e agora, mais o agravante da pandemia. Em meio a todo esse problema, pergunta-se: quem cuida dessas mulheres? Portanto, este trabalho tem como objetivo desenvolver um projeto de serviço, marca e produto que contribua com o desenvolvimento de um espaço de fala, escuta e acolhimento destas profissionais. Para propor soluções para o problema, foi empregada a metodologia do Design Thinking no projeto. O resultado foi o desenvolvimento de um sistema marca - produto - serviço que visa promover esse ambiente de acolhimento, através de: um serviço que tem colabora com a administração de questões emocionais das profissionais; um produto que se relaciona com o movimento de ir às ruas reivindicar direitos; e uma marca que o público se reconhece. [resumo fornecido pelo autor]
Keywords: Design; Violência conjugal; Violência familiar; Profissionais